Handling optimization Framework for Railway Container Terminal based on Vehicle Interconnection. Issue 5 (March 2019) - Bo, Lin; Wang, Li
Abstract: This paper introduces the background and significance of the study on the dispatching optimization of railway container terminal and analyzes the advantages and feasibility of direct loading and unloading, followed by the function layout of the railway container terminal expounded, with the purpose of this paper analyzed separately on three operation processes. The key technology of the Internet of vehicles is briefly introduced. Finally, the overall process of this paper is depicted with five main steps in detail, which are acquiring vehicle networking data, platform development, algorithm implementation, MCU control and solid model display.